Value and Character Education in the Perspective of General Education in Higher Education - Fuadaturrahmah Fuadaturrahmah; Sukma Ningtias; Doni Setiari; Ebenezer Tarigan; Desnor Steven Waruwu; Waruwu Waruwu; Delfin Masna Gulo; Dwi Agillia Putri; Dhea Reni Anggraini (Education Achievement: Journal of Science and Research, 2024)
To effectively address the growing complexity of living conditions, its crucial to use a comprehensive and multidisciplinary approach. Engaging with experts from many scientific fields s crucial for finding tailored answers to complex problems that require knowledge from multiple disciplines. Library research s utilised to investigate and clarify data. This inquiry utilises literature the form of rules to assess the value and character education higher education from a general education perspective. The aim of this study s to examine and offer arguments concerning the subjects of value and character education higher education institutions Indonesia, focusing on the perspective of general education. Here s a brief overview of the findings from this investigation: General education, sometimes known as "liberal education," provides unique answers that are not accessible in other academic disciplines. Moreover, general education has the ability to bring together different academic fields by examining the fundamental concepts of science, which are closely connected to morals and ethics. General education hinders the scientific community's ability to protect tself from other scientific fields or engage in conflicts with each other by presuming that science has any moral or ethical principles. The core focus of general education lies an cultivating values and character, which empower persons who have undergone general education to develop a well-rounded personality and acquire extensive knowledge across various disciplines. This research s expected to encourage individuals to embrace a more open-minded outlook on the accessibility of many areas of study, therefore avoiding the limitation of confining oneself to their present expertise. To be competitive in the constantly changing and sophisticated world, humans must cultivate an enduring inclination to acquire knowledge and engage in continuous study.